Psychometric Validation of the STEM Disciplines Attitude Scale (SDAS): Investigating Measurement Invariance and Psychological Correlates in Italian High School Students - Angelo Fumia; Luana Sorrenti; Carmelo Mario Vicario; Francesca Ferraioli; Simona Massimino; Rosa Angela Fabio; Pina Filippello; Daniele Mollaioli (European Journal of Investigation in Health, Psychology and Education, 2026)
Promoting positive student attitudes toward STEM is essential for fostering innovation; however, many existing measures do not adequately distinguish attitudes across specific disciplines, particularly within hard sciences such as physics and chemistry. This study presents the development and validation of the STEM Disciplines Attitude Scale (SDAS). Across three studies involving 2577 high school students, Exploratory and Confirmatory Factor Analyses supported a 25-item, five-factor structure assessing attitudes toward Mathematics, Physics, Chemistry, Engineering, and Science and Technology. The SDAS showed good internal consistency and strong convergent and discriminant validity. Measurement invariance analyses demonstrated full invariance across grade levels and metric invariance across genders. Gender comparisons indicated more positive attitudes among males in mathematics, physics, engineering, and science and technology, whereas no gender differences emerged in chemistry. Correlational and regression analyses identified Mastery Orientation and Problem-Solving Confidence as positively related to attitudes across several STEM domains. Learned Helplessness and Emotional Control showed more discipline-specific associations, particularly for Mathematics and Engineering. The SDAS fills an important measurement gap by providing a reliable tool for assessing discipline-specific STEM attitudes and their psychological correlates, thereby supporting both research and educational interventions.